2021
DOI: 10.52403/ijrr.20210404
|View full text |Cite
|
Sign up to set email alerts
|

Role of VAC Dressing in the Large Open Fracture: A Single Center Prospective Study from Indore

Abstract: Background: As the body's protective skin barrier is breached in open fractures, and the potential of contamination is high, these can lead to significant morbidity. Vacuum-assisted closure (VAC) is the application of the negative pressure in open wounds, and it significantly improves wound healing both at the macro and micro levels. Material and Method: A total of 30 patients (23 males and 7 females with a mean age of 27 years) with large open fractures of long bones who received VAC therapy during the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The mean delay between the occurrence of trauma and the beginning of debridement was 13.76 minutes, with an SD of 11.492 minutes. In contrast, Suman et al [3] reported that the mean period between the trauma and the first debridement was 8.20 hours (range: 2-23).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The mean delay between the occurrence of trauma and the beginning of debridement was 13.76 minutes, with an SD of 11.492 minutes. In contrast, Suman et al [3] reported that the mean period between the trauma and the first debridement was 8.20 hours (range: 2-23).…”
Section: Discussionmentioning
confidence: 93%
“…This finding was similar to that of Lee et al in Korea [21], who found that the average duration of VAC therapy was 18.4 days (range: 11-29 days). Suman et al [3]. from India reported an average period of VAC application of 10 days (range: 3-16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a fact that severe open fractures were presented with a range of 25-66% infection rate [ 1 - 3 ]. Several determinants are always to be well-thought-out when assessing and treating compound fractures in the extremities, including the patient's condition, fracture type, antimicrobial therapy, wound debridement, site and size of the wound, neurovascular status, and the degree of muscle tear [ 4 , 5 ]. Usually, the Gustilo-Anderson classification model is used to classify the compound fractures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%